Penerapan Metode Karyawisata sebagai Upaya Menumbuhkan Interaksi Sosial pada Mata Pelajaran Sejarah Kebudayaan Islam Siswa Kelas VIII MTs Swasta Tarbiyah Waladiyah Pulau Banyak - Khairuddin YM (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2021)
The purpose of this study was to find out how to apply the method, social interaction and increase social interaction between field trip students in the subject of Islamic culture history for eighth grade students of MTs Swasta Tarbiyah Waladiyah Pulau Banyak. This study uses classroom action research (classroom action research). When educators give tests to students, and get an average score of 64.73. With the number of students who completed as many as 10 (38.46 %), thus the field trip method is very effective to improve student learning outcomes. By using the field trip method, there will be social interaction between students, nature and the environment. This makes students more creative and active, it can be seen in the first cycle obtained an increase in student learning outcomes with an average value of 69.23. With the number of students who completed as many as 18 (69.23%) and the value of observation of student activities 87.5%. The increase in social interaction occurred in the second cycle, it was obtained an increase in student learning outcomes with an average value of 76.73.